Beetles "in red": are the endangered flat bark beetles Cucujus cinnaberinus and C. haematodes chemically protected? (Coleoptera: Cucujidae). Issue 1 (1st January 2018) - Bonacci, T.; Mazzei, A.; Naccarato, A.; Elliani, R.; Tagarelli, A.; Brandmayr, P.
Abstract: Two native species of the genus Cucujus show a wide geographic distribution in Europe, Cucujus cinnaberinus (Scopoli, 1763) and C. haematodes Erichson, 1845. Although data on the distribution and ecology of these rare and endangered species are increasing, there are few reports on their biology and behaviour, and some aspects of their feeding ecology remain problematic. Our aim was to study, for the first time, the cuticular chemical profiles of these two beetles to (i) investigate the presence of chemicals potentially involved in defence by pathogens and (ii) lay the foundation for understanding the role of their bright red colour. The analysis of the cuticular profile was performed in-vivo by solid phase microextraction coupled with gas chromatography-mass spectrometry. In the cuticular profiles of the two species we identified 24 compounds belonging to different classes of molecules, i.e. hydrocarbons, aldehydes, esters, n-alkyl morpholines, and a high number of organic acids. Qualitative differences in terms of both signal intensity and detected compounds were found between the two species. As reported in other insects, the remarkable array of avoidance substances suggests a strict relationship with the bright red colour of the adults, which probably acts as an aposematic or warning signal. European Cucujus species are probably well protected against enemies because some identified chemicals, particularly fatty acids, are related to an anti-predatory strategy to fight off predators that use their sense of smell to locate their prey. Other substances found on the cuticular layer of these beetles are probably involved in an antimicrobial and antifungal function, as demonstrated in other insects living in habitats that host many pathogens.